THE TECHNOLOGY FOR CREATING A TERMINOLOGICAL THESAURUS AND PROSPECTS FOR ITS USE IN EDUCATION (World Bulletin of Education and Learning, 2026)
This article examines the theoretical and methodological foundations for creating terminological thesauri, their linguistic and semantic characteristics, and the possibilities for modeling them using modern information technologies. It explores the systematization of hierarchical, paradigmatic, and semantic relationships between terms. Furthermore, the prospects for automatically generating thesauri with the help of artificial intelligence, machine learning, and natural language processing technologies are substantiated. The research scientifically highlights the significance of terminological thesauri in systematizing knowledge within the educational process, personalizing learning activities, and enhancing the quality of education.
Keywords: Thesaurus, terminology, information technology, artificial intelligence, education, linguistics.